The impact of the AMV on Eurasian summer hydrological cycle - Nicoli', Dario; Bellucci, Alessio; Iovino, Doroteaciro; Ruggieri, Paolo; Gualdi, Silvio (Scientific Reports, 2020)
Impact studies of the Atlantic Multidecadal Variability (AMV) on the climate system are severely limited by the lack of sufficiently long observational records. Relying on a model-based approach is therefore mandatory to overcome this limitation. Here, a novel experimental setup, designed in the framework of the CMIP6-endorsed Decadal Climate Prediction Project, is applied to the CMCC climate model to analyse the remote climate impact of the AMV on the Northern Eurasian continent. Model results show that, during Boreal summer, an enhanced warming associated to a positive phase of the AMV, induces a hemispheric-scale wave-train response in the atmospheric circulation, affecting vast portions of Northern Eurasia. The overall AMV-induced response consists in an upper-tropospheric anomalous flows leading to a rainfall increase over Scandinavia and Siberia and to an intensified river runoff by the major Siberian rivers. A strengthening of Eurasian shelves' stratification, broadly consistent with the anomalous river discharge, is found in the proximity of the river mouths during positive-AMV years. Considering that Siberian rivers (Ob', Yenisei and Lena) account for almost half of the Arctic freshwater input provided by terrestrial sources, the implications of these findings for decadal variability and predictability of the Arctic environment are also discussed. Published 14444 4A. Oceanografia e clima JCR Journal